The Effect Of Communication, Patient Engagement, and Facilities on the Patient Experience at Mother and Child Hospital Tinatapura Palu - Armanto Makmun; Rokiah Kusumapradja; Hasriwiani Habo Abbas (Window of Health : Jurnal Kesehatan, 2026)
Patient experience is an important indicator of healthcare quality because it reflects how patients perceive communication, involvement in care, and the healthcare environment. This study aimed to examine the influence of communication, patient involvement, and facilities on patient experience among outpatient service users at RSIA Tinatapura Palu. An analytical observational study with a cross-sectional design was conducted from August to September 2025. Using accidental sampling, 111 respondents were recruited from a population of 154 outpatients. Data were collected using a structured questionnaire measuring communication, patient involvement, facilities, and patient experience. Data were analyzed using descriptive statistics, classical assumption tests (normality, multicollinearity, and heteroscedasticity), and multiple linear regression at the 0.05 significance level. The analysis showed that communication (β = 0.443; p = 0.003), patient involvement (β = 0.326; p = 0.020), and facilities (β = 0.490; p < 0.001) were each significantly and positively associated with patient experience, with facilities demonstrating the strongest standardized effect. The overall regression model was statistically significant (F = 21.925; p < 0.001) and explained 38.1% of the variance in patient experience (R² = 0.381), indicating moderate explanatory power. These findings suggest that strengthening provider–patient communication, promoting patient involvement in care, and improving outpatient facilities should be prioritized in continuous quality improvement initiatives to enhance the patient experience.